Progress of research on stressors and coping styles of newly graduated nurses (新毕业护士压力源及应对方式研究进展) - ZHANG Na (张娜); TAO Yuexian (陶月仙); ZHOU Qi (周琪); ZHANG Jiayu (张佳宇) (Association of Integrative Nursing, 2024)
Newly graduated nurses suffer from occupational stress during the transition from school to employment, leading to the negative emotion, job burnout and increased turnover rate. This article aims to give a general picture of the pressures and coping styles faced by newly graduated nurses, identifies gaps in existing stress-reducing interventions for newly graduated nurses with a view to facilitating the transition of newly graduate nurses and preventing the loss of nursing human resources. (新毕业护士会面临各种压力, 导致出现负面情绪、职业倦怠, 增加离职率。本文综述新毕业护士的压力源及其应对方式, 指出现存减轻新毕业护士压力干预的不足, 以期促进新毕业护士的转型, 防止护理人力资源流失。)